Training wheelchair navigation in immersive virtual environments for patients with spinal cord injury – end-user input to design an effective system. (19th May 2017) - Nunnerley, Joanne; Gupta, Swati; Snell, Deborah; King, Marcus
Abstract: Purpose: A user-centred design was used to develop and test the feasibility of an immersive 3D virtual reality wheelchair training tool for people with spinal cord injury (SCI). Method: A Wheelchair Training System was designed and modelled using the Oculus Rift headset and a Dynamic Control wheelchair joystick. The system was tested by clinicians and expert wheelchair users with SCI. Data from focus groups and individual interviews were analysed using a general inductive approach to thematic analysis. Results: Four themes emerged: Realistic System, which described the advantages of a realistic virtual environment; a Wheelchair Training System, which described participants' thoughts on the wheelchair training applications; Overcoming Resistance to Technology, the obstacles to introducing technology within the clinical setting; and Working outside the Rehabilitation Bubble which described the protective hospital environment. Conclusions: The Oculus Rift Wheelchair Training System has the potential to provide a virtual rehabilitation setting which could allow wheelchair users to learn valuable community wheelchair use in a safe environment. Nausea appears to be a side effect of the system, which will need to be resolved before this can be a viable clinical tool. Implications for Rehabilitation: Immersive virtual reality shows promising benefit for wheelchair training in a rehabilitation setting. Early engagement with consumers can improve product development.